Raising the Bar for Productive Cities in Latin America and the Caribbean - Ferreyra, Maria Marta; Roberts, Mark (Washington, DC: World Bank, 2018)
With more than 70 percent of its population living in cities, Latin America and the Caribbean (LAC) is among the most urbanized regions in the world. Yet, although its cities are, on average, more productive than those elsewhere in the world, their productivity lags that of North American and Western European cities. Closing this gap provides LAC with the opportunity to raise living standards and join the ranks of the world’s richest countries.